First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Multicomponent Reaction Based Tolyl-substituted and Pyrene-Pyridine Conjugated Isomeric Ratiometric Fluorescent Probes: A Comparative Investigation of Photophysical and Hg(II)-Sensing Behaviors - Raghvendra Niranjan; G. Durga Prasad; Simi Achankunju; Mariyaraj Arockiaraj; Kotteswaran Velumani; Kiruthika Nachimuthu; Ashok K. Sundramoorthy; Ishita Neogi; Jothi L. Nallasivam; Venkatachalam Rajeshkumar; Surendra H. Mahadevegowda (Journal of Fluorescence, 2024)

Latent heat flux variation during the warming phase of intraseasonal oscillations over northern Bay of Bengal - Simi Mathew; G Latha; R Venkatesan (Journal of Earth System Science, 2020)

Management Options to Improve Water Quality in Lake Peipsi: Insights from Large Scale Models and Remote Sensing - Gabriel Fink; Sophia Burke; Stefan G. H. Simis; Külli Kangur; Tiit Kutser; Mark Mulligan (Water Resources Management, 2020)

Optical types of inland and coastal waters - Evangelos Spyrakos; Ruth O'Donnell; Peter D. Hunter; Claire Miller; Marian Scott; Stefan G. H. Simis; Claire Neil; Claudio C. F. Barbosa; Caren E. Binding; Shane Bradt; Mariano Bresciani; Giorgio Dall'Olmo; et al. (Limnology and Oceanography, 2018)
Inland and coastal waterbodies are critical components of the global biosphere. Timely monitoring is necessary to enhance our understanding of their functions, the drivers impacting on these functions and to deliver more effective management. The ability to observe waterbodies from space has led to Earth observation (EO) becoming established as an important source of information on water quality and ecosystem condition. However, progress toward a globally valid EO approach is still largely hampered by inconsistences over temporally and spatially variable in‐water optical conditions. In this study, a comprehensive dataset from more than 250 aquatic systems, representing a wide range of conditions, was analyzed in order to develop a typology of optical water types (OWTs) for inland and coastal waters. We introduce a novel approach for clustering in situ hyperspectral water reflectance measurements ( n = 4045) from multiple sources based on a functional data analysis. The resulting classification algorithm identified 13 spectrally distinct clusters of measurements in inland waters, and a further nine clusters from the marine environment. The distinction and characterization of OWTs was supported by the availability of a wide range of coincident data on biogeochemical and inherent optical properties from inland waters. Phylogenetic trees based on the shapes of cluster means were constructed to identify similarities among the derived clusters with respect to spectral diversity. This typification provides a valuable framework for a globally applicable EO scheme and the design of future EO missions.

Implementing and Innovating Marine Monitoring Approaches for Assessing Marine Environmental Status - Roberto Danovaro; Laura Carugati; Marco Berzano; Abigail E. Cahill; Susana Carvalho; Anne Chenuil; Cinzia Corinaldesi; Sonia Cristina; Romain David; Antonio Dell'Anno; Nina Dzhembekova; Esther Garcés; et al. (Frontiers in Marine Science, 2016)

Colorectal delivery and retention of PEG-Amprenavir-Bac7 nanoconjugates—proof of concept for HIV mucosal pre-exposure prophylaxis - Mahta Samizadeh; Xiaoping Zhang; Simi Gunaseelan; Antoinette G. Nelson; Matthew S. Palombo; Daniel R. Myers; Yashveer Singh; Usha Ganapathi; Zoltan Szekely; Patrick J. Sinko (Drug Delivery and Translational Research, 2016)

Optimization of variable fluorescence measurements of phytoplankton communities with cyanobacteria - Stefan G. H. Simis; Yannick Huot; Marcel Babin; Jukka Seppälä; Liisa Metsamaa (Photosynthesis Research, 2012)

Optical signatures of the filamentous cyanobacterium Leptolyngbya boryana during mass viral lysis - Stefan G. H. Simis; Marjolijn Tijdens; Hans L. Hoogveld; Herman J. Gons (Limnology and Oceanography, 2007)
The inherent optical properties of absorption and scattering, the population density of virus‐like particles, and the particle size distribution (PSD) for particles Leptolyngbya boryana were monitored for 72 h at 9‐h intervals following infection with cyanophage LPP‐1. Lorenz‐Mie scattering theory and the anomalous diffraction approximation were used to derive the refractive index representative of the bulk of particles and to model the particulate backscattering coefficient [ b bp (λ)]. Upon lysis, particulate absorption [ a p (λ)] and scattering [ b bp (λ)] decreased, the number of free virus‐like particles increased drastically, the PSD shifted to relative abundance of small particles, and average trichome length decreased sharply. The complex refractive index of the bulk of particles was comparable with literature values for cyanobacteria. Modeled b bp (λ) spectra were lowered upon lysis, while backscattering probability increased. The effect of underrepresentation of particles below the measurement limit of the particle sizer was studied; more small particles in the PSD resulted in higher, but still relatively low, backscattering probability. The consequences of the studied optical behavior on spectral reflectance was explored. Significant spectral changes at longer wavelengths were mostly masked by water absorption at nominal population densities. However, strongly reduced a p (λ) in the red pigment absorption bands resulted in a pronounced green peak in reflectance spectra, and it was concluded that reflectance band ratio algorithms targeted at the absorption of the pigments phycocyanin and chlorophyll a can be used to detect the mass mortality caused by viral infection. The integrated intensity of reflected light was too variable to serve as an optical indicator for lytic events.